2004
DOI: 10.1111/j.1365-3156.2004.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

DEET mosquito repellent provides personal protection against malaria: a household randomized trial in an Afghan refugee camp in Pakistan

Abstract: SummarySynthetic repellents based on di-ethyl 3-methyl benzamide (DEET) are a popular method of obtaining protection from mosquitoes and yet clear evidence for a protective effect against malaria has hitherto never been convincingly demonstrated. A household randomized trial was undertaken among a study population of 127 families (25%) in an Afghan refugee village in Pakistan to compare the efficacy of repellent soap (Mosbar TM containing 20% DEET and 0.5% permethrin) vs. a placebo lotion. Cases of falciparum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 19 publications
(37 reference statements)
3
101
0
Order By: Relevance
“…The mosquito repellent used, Mosbar, was accepted by the community and had very few sideeffects. [5] In our study, staying indoors was found to be protective against contracting malaria. Conversely, outdoor activity increased the risk of contracting malaria.…”
Section: Discussionmentioning
confidence: 85%
“…The mosquito repellent used, Mosbar, was accepted by the community and had very few sideeffects. [5] In our study, staying indoors was found to be protective against contracting malaria. Conversely, outdoor activity increased the risk of contracting malaria.…”
Section: Discussionmentioning
confidence: 85%
“…This technique has been used to estimate the size of area-wide effects in studies of LLINs for malaria control [61]. Unintended consequences of topical repellents can be avoided by randomising only a relatively low proportion of individuals or households in a village to receive the intervention [31,62,63]. Tackling the problem of human movement in dengue studies is more difficult because Aedes aegypti feeds during the day when people are engaged in their daily activities.…”
Section: Selection Of Sites For Entomological Monitoringmentioning
confidence: 99%
“…It is a reasonable supposition that they also reduce malaria transmission, and some evidence to confirm this is now becoming available (Durrheim and Govere, 2002;Rowland et al, 2004). However, the cost of daily use of synthetic repellents is not affordable in malaria endemic areas, as they would have to be applied at least twice every night during the malaria season to give protection throughout the biting time of malaria vectors.…”
Section: Introductionmentioning
confidence: 94%